ANALISIS STATUS GIZI DAN PERKEMBANGAN MOTORIK KASAR ANAK USIA 4–5 TAHUN DI TK KENTEN PERMAI PALEMBANG - Nurbaity; Heolen Meiliza Putri (LPPM STIKes Mitra Adiguna, 2026)
Nutritional status is an important indicator in determining children's health and development, as developmental disorders in preschool age can affect the learning process at school. This study aimed to analyze the nutritional status and gross motor development of children aged 4–5 years at TK Kenten Permai Palembang. The method used was quantitative research with a cross-sectional design. The population was 70 children, and a sample of 30 children was taken using purposive sampling technique. Data were collected using the DDST (Denver Development Screening Test) sheet and anthropometric measurements, then analyzed using the Chi-square test. The results showed that most children had normal nutritional status (46.7%) and normal gross motor development (86%). The statistical test obtained a p-value = 0.420 (> 0.05). The conclusion of this study is that there is no significant relationship between nutritional status and gross motor development of children aged 4–5 years at TK Kenten Permai Palembang.